ANALISIS CD4 PADA PENATALAKSANAAN PASIEN KOINFEKSI HIV-TB - Nursin Abd. Kadir; Nurhayana Sennang; Hardjoeno . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
The Human Immunodeficiency Virus (HIV) epidemic has increased the burden of tuberculosis (TB) among young adults, especially in populations where the prevalence of TB infection is high like Indonesia. TB is the most common opportunistic infection on HIV patients(50%) in developing countries. CD4 also known as T helper lymphocytes are coordinators of body`s immune response, and it has beendeclining in HIV infection and be worsened by TB infection. CD4 count are standard laboratory marker of disease progression to followupandprognosisantiretroviraltherapyinHIVinfection.AimstoseethevalueofCD4countofHIV-TBco-infectedpatientsbeforeandafterantituberculosistogetherwithantiretroviraltherapy.AlongitudinalstudywasconductedbycollectingsecondarydatafromthemedicalrecordandtheresultsofClinicalPathologyLaboratoryofHIV-TBco-infectedpatientsatWahidinSudirohusodoHospitalperiodJuly2007–August2008.DatawereanalyzedbyWilcoxonSignedRankTestandMannWhitneyTestwitha=0.05.Totalsamples(n)were20patients(14patientswithcontinoustherapyand6uncontinoustherapy).WefounddifferentmeansbetweenCD4countbeforeandafterTherapy.CD4countbeforetherapywas71.15±81.04andaftertherapywas114.95±109.71(p=0.089)withWilcoxonSignedRankTest.Theanalyzedwerecontinuedbydividedsamplesincontinousgroupcomparedwithuncontinousgrouptherapy.TheresultshowedtheCD4alterationincontinousgroupwas853.8%anduncontinousgroupwas-56.6%wherep=0.000(MannWhitneytest).CD4counthasincreasedsignificantlyinHIV-TBco-infectedpatients8.5foldfromCD4baselinewithcontinoustherapyandtheuncontinous one has decreased 0.5 fold from CD4 baseline.